Estimación del índice de agresividad climática bajo escenarios de cambio climático en la cuenca de Ubaté y Suárez (2016)
This study evaluated the aggressiveness of precipitation using the Fournier Index – IF, Modified Fournier Index – IMF and precipitation concentration index – ICP, in the Ubaté – Suárez Basin in the departments of Cundinamarca and Boyacá, and its future behavior considering climate change scenarios, established by the Intergovernmental Panel on Climate Change – IPCC and adopted in Colombia by the  National Institute of Hydrology, Meteorology and Environmental Studies – IDEAM.  The analysis was carried out over two different time scales decennial and inter-annual, in which it was concluded that the climatic aggressiveness indexes are greater for the current period (1971-2010), with respect to the predicted data in climate change scenarios, furthermore in IF at least 70% of the territory exceeded a value of 200mm which indicates a very high level of aggressiveness, whereas for the IMF in 100% of cases, independently of the different climate change scenarios applied and periods, had a very high level of climate aggressiveness exceeding by far the limit of 400m, as for the ICP, it shows moderately seasonal to uniform values in the different scenarios and periods.